Fabrication, development and analysis of film bulk acoustic resonators on flexible polymer substrates - Hakemi, Ghazal (Cranfield University, 2010)
It is the focus of this project to explore the possibility of achieving Radio Fre¬quency (RF) micro-devices on flexible polymer substrates. To this end standard MEMS fabrication methods have been tailored to allow the integration of func¬tional materials and device patterning for production of RF MEMS devices with flexible organic substrates. Material quality, device yield, performance and re-liability are critical aspects of our study. The project encompasses the use of a direct integration method for the creation of Film Bulk Acoustic Resonators (FBARs) on Liquid Crystal Polymer (LCP) substrates. An FBAR is a passive component used for resonance and filtering purposes. Its production on organic substrates would lead to a number of ad-vantages including: overall cost savings, size reduction and ability of the device to be directly integrated on the printed circuit board (PCB) front-end with the other essential components (i.e. antenna) without the use of wiring and inter-connections. New fabrication process flows have been developed to allow the creation of FBAR microwave devices on LCP. First of all pre-processing of the polymer substrate is carried out to make it rigid and smooth. Substrate smoothness and stiffness are necessary in order to obtain functioning devices and for the substrate to comply to the standard fabrication methods. Rigidity is achieved through a backing method whereby silicon or glass are attached to LCP with an intermediate adhesive layer. The best way to achieve smoothness was found to be Chemical Mechanical Polishing (CMP). Standard fabrication techniques were then employed to deposit the metal and piezoelectric material and pattern them. Both bulk and surface micromachining were used and, in some cases, tailored to suit the new substrates (LCP) tolerance limits (such as temperature and flexibility). Zinc Oxide (ZnO) piezoelectric is the preferred functional material and it is chosen due to its relatively low deposition temperature re¬quirements (below 300C) and its high frequency characteristics. The creation of a front-to-back processed FBAR on LCP is successfully carried out at relatively low temperatures since the Zinc oxide (ZnO) functional mate¬rial is proven to yield good crystallinity at a deposition temperature of 100C and also because micromachining temperatures do not generally exceed 115C. The final device is characterized through RF measurements, compared with sim¬ulations and standard FBARs and the polymer/ceramic integration reliability for device creation is briefly addressed. In conclusion FBARs are successfully created on LCP with only minor compli¬cations related to LCP surface roughness and RIE etch of the polymer. The project lays promising prospects for RF MEMS devices on compliant organic substrates.